2019
DOI: 10.31557/apjcp.2019.20.10.3181
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, Attitudes and Clinical Approach of Lebanese Physicians Towards HPV Vaccination; A Cross- Sectional Study

Abstract: Objectives: HPV infection is associated with the development of cervical and oropharyngeal cancer. HPV vaccination prevents cervical cancer, but is still not part of Lebanon's routine vaccination schedule. As such, understanding physicians' practice towards HPV vaccination is essential. Material and Methods: We conducted a cross-sectional study in Greater Beirut, Lebanon to assess the barriers, attitudes and clinical approach of Lebanese physicians towards HPV vaccination. We also aimed to analyze the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
5
17
0
Order By: Relevance
“…The knowledge regarding risk factor is very low when compared with similar study done at Hawassa University which showed 49.7% and 47.4% respectively on the two risk factors mentioned above and most of the students did not know the major risk factor which is HPV (3.9%). This may be due to lack of detailed health education on the subject matter [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge regarding risk factor is very low when compared with similar study done at Hawassa University which showed 49.7% and 47.4% respectively on the two risk factors mentioned above and most of the students did not know the major risk factor which is HPV (3.9%). This may be due to lack of detailed health education on the subject matter [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based study carried out by Adjei There are differences in information level and opinions of doctors regarding infections associated with HPV and HPV vaccination issues (13)(14)(15)(16)(17). For instance, in our study, a higher percentage of male resident physicians thought that HPV infection may be transmitted only by…”
Section: Family Medicine Resident Physicians Working In the Education And Training Hospitals(fmrp-h)family Medicine Resident Physicians Wmentioning
confidence: 51%
“…Opposition of doctors to HPV vaccination or their nonrecommendation of the vaccine routinely stems from different reasons. These include (i) incorrect or incomplete information about HPV or the HPV vaccine, (ii) non-inclusion of the HPV vaccine in the routine vaccination schedule of the health ministry, (iii) high cost of the vaccine, (iv) absence of widespread acceptance for the vaccine, (v) the opinion that vaccination may increase the prevalence of risky sexual behavior, and (vi) lack of confidence in the efficacy of the vaccine(13)(14)(15)(16)(17). Abi Jaoude et al(17) have shown that opposition to HPV vaccination is significantly lower among doctors with a high level of knowledge.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This con rms ndings of previous studies, that found that 34% of adults were aware of the cancer risks of HPV, and 18.2% of adults were su ciently educated concerning HPV infection. [20][21][22] Sedentary lifestyle Prevalence sedentary lifestyle among Lebanese adults is high: 60.7% of men and 61.3% of women do not meet WHO recommendations on physical activity. [13] Physical inactivity is responsible for 0.6% of cancers in men and 3.2% in women.…”
Section: Hpvmentioning
confidence: 99%